Minimally invasive techniques for lateral maxillary sinus floor elevation: small lateral window and one-stage surgery-a 2-5-year retrospective study - Shaojingya Gao; Yao Jiang; Yangxue Yao; Songhang Li; Xiaoxiao Cai (Nature Publishing Group, 2023)
Abstract This study aimed to introduce a minimally invasive technique for maxillary sinus floor elevation using the lateral approach (lSFE) and to determine the factors that influence the stability of the grafted area in the sinus cavity. Thirty patients (30 implants) treated with lSFE using minimally invasive techniques from 2015 to 2019 were included in the study. Five aspects of the implant (central, mesial, distal, buccal, and palatal bone heights [BHs]) were measured using cone-beam computed tomography (CBCT) before implant surgery, immediately after surgery (T0), 6 months after surgery (T1), and at the last follow-up visit (T2). Patients' characteristics were collected. A small bone window (height, (4.40 ± 0.74) mm; length, (6.26 ± 1.03) mm) was prepared. No implant failed during the follow-up period (3.67 ± 1.75) years. Three of the 30 implants exhibited perforations. Changes in BH of the five aspects of implants showed strong correlations with each other and BH decreased dramatically before second-stage surgery. Residual bone height (RBH) did not significantly influence BH changes, whereas smoking status and type of bone graft materials were the potentially influential factors. During the approximate three-year observation period, lSFE with a minimally invasive technique demonstrated high implant survival rate and limited bone reduction in grafted area. In conclusion, lSFE using minimally invasive techniques was a viable treatment option. Patients who were nonsmokers and whose sinus cavity was filled with deproteinized bovine bone mineral (DBBM) had significantly limited bone resorption in grafted area.